Iowa Birdline update, November 12-15, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Email of the Iowa Birdline update for November 12-15, 1990. Highlights of the update include sightings of Pacific Loon, a first winter Black-legged Kittiwake, a Surf Scoter, a first winter Thayer's Gull, and an immature Golden Eagle. Other observations of note were of a very late Scarlet Tanager, 2 Carolina Wrens, 2 Rough-legged Hawks, and 5 Bald Eagles. Epson - sheet feed/flatbed